The Impact of Recent OJK Regulations on Transparency, Efficiency, and Investor Protection in Indonesia’s Capital Market - Martin, Katrina (Anthology: Inside Intellectual Property Rights, 2025)
This study explores how recent regulations introduced by Indonesia’s Financial Services Authority (Otoritas Jasa Keuangan, or OJK) have influenced transparency, efficiency, and investor protection in the country’s capital market. Using a mixed-methods approach and combining quantitative analysis of market performance with qualitative insights from policy reviews, the research evaluates the impact of these regulatory changes. The findings suggest that OJK’s initiatives, including enhanced disclosure requirements, digital reporting systems, and simplified compliance procedures, have significantly improved market transparency and helped build investor confidence. Efficiency has also improved, with lower transaction costs and faster regulatory approvals thanks to greater automation and better policy alignment.[1] Moreover, stronger oversight and expanded investor education programs have contributed to better protection, especially for retail investors. Despite these gains, challenges remain, such as inconsistent implementation, limited resources, and compliance issues among smaller market participants. Overall, while OJK’s reforms mark important progress in modernizing Indonesia’s capital market, further efforts are needed to tackle structural issues. The study recommends ongoing policy refinement, stronger institutional collaboration, and targeted support for underserved groups. It highlights the importance of adaptive regulation in promoting sustainable market growth while managing risks, offering valuable lessons for policymakers in other emerging markets.